Use of a Piezo Drill for Intracytoplasmic Sperm Injection into Cattle Oocytes Activated with Ionomycin Associated with Roscovitine - Devito, L. G. [UNESP]; Fernandes, C. B. [UNESP]; Blanco, I. D. P. [UNESP]; Tsuribe, P. M.; Landim-Alvarenga, Fernanda da Cruz [UNESP] (Wiley-Blackwell, 2010)
Intracytoplasmic sperm injection (ICSI) consists of the introduction, by micromanipulation, of a single sperm into the cytoplasm of a mature egg. This technique is particularly advantageous when only a few sperm are available for fertilization, representing an important tool in preserving genetic material, especially from poorly fertile males. The results from ICSI in cattle are very often unsatisfactory and difficult to reproduce. Thus, the goal of this study was to evaluate the effect of the use of a Piezo drill (PD) and oocyte activation with ionomycin + roscovitine (I + R) during ICSI in cattle oocytes. After in vitro maturation (24 h), cumulus complex oocytes were divided into four groups: G1 - the ICSI was performed without the use of a PD and the oocyte was activated with I + R; G2 - the ICSI was performed with the use of the PD and activation with I + R; G3 - the ICSI was performed with the use of the PD, but without activation and G4 - parthenogenetic control, treated with I + R, but without sperm injection. The presumptive zygotes were cultured for 7 days and evaluated on day 3 for cleavage rate and on day 7 for blastocyst formation. Embryo production by standard in vitro fertilization in the laboratory was 78% for cleavage (117/150) and 35% for blastocyst formation (41/150). The cleavage rates obtained in G1, G2 and G4 were similar (66.7%, 71.6% and 66.3%, respectively), demonstrating the beneficial effect of oocyte activation. However, in G3, despite the presence of the sperm and the electric stimulation of a PD, the cleavage rates were significantly lower (17.5%) compared with the groups that used chemical activation, even in the absence of sperm (G4). Despite the beneficial effects of activation, this stimulus alone, or in the absence of the PD, was not sufficient for adequate morulae formation (13.4%, 37.9%, 0.0% and 13.5% for G1, G2, G3 and G4, respectively). Only in G2, when the PD was used followed by artificial activation, blastocysts were obtained (14.7%). These results indicate that cattle oocytes must be activated after ICSI to produce viable embryos.